ANALISIS DAUR HIDUP PRODUK (PRODUCT LIFE CYCLE) BIHUN TAPIOKA DI PROVINSI LAMPUNG - Rizky Fitrianingsih Dalimunthe; Wuryaningsih Dwi Sayekti; Ani Suryani (Lampung University, 2020)
This research aims to analyze the position of tapioca vermicelli production on the product life cycle (PLC), to know the manufacturer’s perception of the development of tapioca vermicelli business, and correlation between the perception and the PLC. This research used a case study method at tapioca vermicelli industries, namelySinar Jaya (SJ), SinarHarapan (SH), Monas Lancar (ML), Bintang Obor (BO), and Moro Seneng (MS). Respondents are the owners of the agroindustries. Data were analyzed using a descriptive statistical analysis and qualitative descriptive. The results showed that the positions of tapioca vermicelli product in terms of the product life cycle in SJ, ML, and MSare in the Growth Stage, while those of SH and BO are at the Maturity Stage. Business development is perceived as important by producers, but it is difficult to do. There is no correlation between perceptions of the development of the business and the product life cycle.Keywords: perception, PLC, tapioca vermicelli.